Efeito de nanocápsulas contendo curcumina no comportamento tipo depressivo e no estresse oxidativo induzidos por β-amilóide em camundongos - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Alzheimer's disease is a neurodegenerative disorder classically characterized by impairment of cognitive functions. However, depression is one of the most frequent behavioral changes observed in the Alzheimer’s disease symptomatology. AD development includes inflammation and oxidative stress resulting from the Aβ protein accumulation in the brain. Curcumin shows antioxidant and anti-inflammatory properties but it has low bioavailability. In this context, the use of curcumin’s nanocapsules (NLC C) emerges. Thus, the aim this study was to investigate the effects of NLC C on the depressive behavior and oxidative stress induced by an animal model of AD. For this, Swiss male mice were divided into five groups and only the Aβ, Aβ+NLC C and Aβ+Curcumin groups received intracerebroventricular injection of the Aβ25-35 aggregate. Control and NLC C groups received only vehicle. The NLC C were administered via gavage at a dose of 10 mg/kg in alternate days for 12 days. Our results showed that Aβ infusion induced a depressive-like behavior observed in the tail suspension test and forced swimming test, which were reversed by NLC C treatment. Furthermore, NLC C was able to restore the Aβ-generated oxidative stress in the prefrontal cortex, evidenced by the increase in the reactive species levels, superoxide dismutase and catalase activities. Importantly, NLC C displayed superior effects than the free form of curcumin. Thus, we demonstrated the antidepressant-like and antioxidant effects of NLC C in a mice model of AD, suggesting its therapeutic potential for this disorder.
Effect of nanocappsules containing curcumin on depressive type behavior and oxidative stress induced by β-amyloid in mice
Keywords: Nanocápsulas; Estresse oxidativo; Alzheimer's disease; Curcumin; Depression; Nanocapsules; Oxidative stress; Doença de Alzheimer; Curcumina; Depressão; CNPQ::CIENCIAS BIOLOGICAS